Definition of bulky disease in early stage diffuse large B-cell lymphoma in computed tomography on coronal and transverse planes - Ma’koseh, Mohammad; Farfoura, Heba; Khatib, Yumna; Omari, Zaid; Ababneh, Hazim; Fayoumi, Baha A.; Taqash, Ayat; Al-Rwashdeh, Mohammad; Abufara, Alaa; Shahin, Omar; Halahleh, Khalid; Al-Rabi, Kamal (Frontiers in Oncology, 2023)
In early stage diffuse large B cell lymphoma (ESDLBL), tumor bulkiness is an important determinant of treatment and prognosis. Tumor bulk is usually measured on transverse computed tomography (CT) plane and variably defined from five to ten centimeters.Our study aims to investigate the prognostic significance of bulky disease measured on CT coronal and transverse planes and to evaluate the outcome of patients with bulky disease.Patients with ESDLBL and treated with RCHOP with or without radiotherapy were included.Receiver Operating Characteristic (ROC) analysis was used to identify the optimal tumor dimension that correlated with progression, relapse, or death. Correlation between different variables and progression free survival (PFS) and overall survival (OS) were analyzed using Log-rank (Mantel-Cox) test and Cox proportional hazard models.A total of 127 patients with a median age of 47 (range: 18-90) years were included. 82 (64.6%) patients treated with combined modality treatment (CMT) [RCHOP + radiotherapy].After a median follow-up of 40 (range 2-114) months, 3-year PFS and OS were 83.9% (95% CI: 76.759%-89.981%), and 80.6% (95% CI: 72.499%-87.531%), respectively. Tumor dimension of > 7.5 cm measured on either CT plane was the optimal cut-off point to define bulky disease. 3-year PFS and OS were inferior in the group of patients with no bulky disease on transvers plane (n=84) but had bulky disease on coronal plane (n=9,10.7%) ; (94.2% vs 75%, p=0.017 and 90.5% vs 56.3%, p=0.002), as well as in patients with no bulky disease on coronal plane (n=89), but had bulky disease on transverse plane (n=14, 15.7%) ; (94.1% vs 62.3%, p<0.001, and 90.4% vs 63.5%, p=0.002). Compared to RCHOP alone, 3-year PFS and OS were better in patients with bulky disease treated with CMT (78% vs 52.5%, p=0.018 and 81.8% vs 38.7%, p=0.003) but not in patients with non-bulky disease (96.2% vs 93%, p=0.691 and 87.6% vs 91.5%, p=0.477).In ESDLBL, measurement of tumor mass on transverse and coronal CT planes may help in better identification of patients with bulky disease. The use of CMT was associated with better survival outcomes in patients with bulky disease.